2013
DOI: 10.4103/2249-4863.120753
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity pattern and personal hygiene in children among private primary school in urban area: Are the trends changing?

Abstract: Introduction:School health is an important intervention as a great deal of research tells us that schools can have a major effect on children's health, by teaching them about health and promoting healthy behaviors.Aims:The aim of this study is to determine common health problems and assess personal hygiene status among primary school children.Settings and Design:A cross-sectional study was conducted in academic years 2009-2010 and 2010-2011, with three health check-up camps organized in private primary school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 1 publication
(2 reference statements)
3
16
2
Order By: Relevance
“…This result is in conformity with Ahmed et al, (2008) [18] in their study which showed that, male gender (10.4%) was significantly more susceptible to diarrhoea than females (8.1%) [17]. This might be due to the finding that, females are more conscious of hygienic practices and hence maintain personal hygiene than males as reported by Mhaske Mayavati S. et al, (2013) [22] in their study in which hygiene score for skin and clothes was significantly poor in males compared to female school children in India. But this finding is in contrast with that of Syed MS. et al, (2003) [23] in which females had marginally higher prevalence of diarrhoea than males in their study of estimating the prevalence and correlates of diarrhoea among children under three years in remote rural villages of South Pakistan.…”
Section: Discussionsupporting
confidence: 88%
“…This result is in conformity with Ahmed et al, (2008) [18] in their study which showed that, male gender (10.4%) was significantly more susceptible to diarrhoea than females (8.1%) [17]. This might be due to the finding that, females are more conscious of hygienic practices and hence maintain personal hygiene than males as reported by Mhaske Mayavati S. et al, (2013) [22] in their study in which hygiene score for skin and clothes was significantly poor in males compared to female school children in India. But this finding is in contrast with that of Syed MS. et al, (2003) [23] in which females had marginally higher prevalence of diarrhoea than males in their study of estimating the prevalence and correlates of diarrhoea among children under three years in remote rural villages of South Pakistan.…”
Section: Discussionsupporting
confidence: 88%
“…These findings were similar to those found by Amit Kaushik et al, (7) (46%). The incidence was lower than that reported by M S Mhaske et al, (11) (65.1%) but higher than that reported by V Rani et al, (12) (36.25%), S Ananthakrishnan et al, (13) (27.9%), P Panda et al, (14) (23.1%) and Shakya et al, (15) (19.8%).…”
Section: Discussioncontrasting
confidence: 54%
“…8,15 Cases of scabies were found among 3.1% of students which was similar to that reported by Sehgal R et al (3.09%), Berard AS et al (2.8%) and Sambo MN et al (2.9%). 15,8,9,18 Acute respiratory tract infection was detected among 21.9% children in the present study which was similar to that reported by Saluja N et al (23.4%) and Karikatti et al (22.57%). 14,19 Ear discharge was detected among 3.9% children in our study which was more than that reported by Sehgal R et al (2.85%), Ananthakrishnan S et al (3.1%) but much less than that reported by Kaushik A et al (13.6%) and Tiwari HC et al (21.5%).…”
Section: Discussionsupporting
confidence: 91%
“…However, study by Mhaske et al, has reported morbidity among boys is higher as compared to girls. 9 The magnitude of pallor in the present study was 47.6%, which was similar to that reported by Devi P et al (50.15%), but more than that reported by Tiwari HC et al (33.9%), Semwal et al (28.4%), Panda et al (26%) and Hassan et al (24.8%). [10][11][12][13]2 In our study, more number of female students had pallor than the male students and similar findings were reported in all other studies as well.…”
Section: Discussionsupporting
confidence: 89%